2020
DOI: 10.1101/2020.02.16.951491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid learning of the 5-choice serial reaction time task in an automated rodent training system

Abstract: 11Experiments aiming to understand sensory-motor systems, cognition and behavior often require animals 12 trained to perform complex tasks. Traditional training protocols require lab personnel to move the animals 13 between home cages and training chambers, to start and end training sessions, and in some cases, to 14 hand-control each training trial. Human labor not only limits the amount of training per day, but also 15 introduces several sources of variability and may increase animal stress. Here we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…five-choice serial reaction time task 36 . Before the surgery, the animals were pretrained for 5-10 days in an automated system 37 (see "Methods"). By the end of the pretraining period, all animals learned the task and performed at around 80% accuracy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…five-choice serial reaction time task 36 . Before the surgery, the animals were pretrained for 5-10 days in an automated system 37 (see "Methods"). By the end of the pretraining period, all animals learned the task and performed at around 80% accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Poking during the ITI, choosing an incorrect port, or omitting a response was punished by a 5-s-long timeout, during which the house light was turned off and no new trial was started. All mice were pretrained before the surgery in a custom-built automated training system 37 , where they were allowed to enter the training setup from their home cages and perform the task regularly every 2 h for 15 min (12 times a day), until they reached 80% performance (5-10 days). After 1 week of recovery period following the surgery, postoperative CT scans were performed in the case of the test group (n = 7, allocated randomly), and the behavioral training was resumed.…”
Section: Methodsmentioning
confidence: 99%
“…The 5-CSRTT quantifies attention, impulsivity, and cognitive flexibility in preclinical models for ASD. Several previous studies have shown the construct validity of the 5-CSRTT as a model for attention [ 41 , 44 ]. Due to the equalized effects of genetic and environmental risk factors, it was initially hypothesized that Cntnap2 deficiency would interact with poly I:C MIA to exacerbate ASD-related attentional alterations seen in each model individually.…”
Section: Discussionmentioning
confidence: 99%
“…A 20-30 s intertrial interval would allow mice to finish eating rewards on most trials (Figure 5B). Alternatively, water rewards could be used instead of pellet rewards (Birtalan et al, 2020). Additionally, the 5CSRTT can be automated to allow ad libitium 24 h access to the task via a tube connecting the homecage to the testing chamber (Remmelink et al, 2017;Bruinsma et al, 2019).…”
Section: Discussionmentioning
confidence: 99%